2012
DOI: 10.1007/s12070-011-0432-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for a Good Outcome Following Endoscopic Sinus Surgery

Abstract: The aim of this study was to establish if there are any symptoms which can predict increased patient satisfaction following Endoscopic Sinus Surgery (ESS) and whether these symptoms correlate with Lund-Mackay score on Computerised Tomography (CT). A prospective observational study was performed. Ninety-three consecutive patients who were offered ESS were recruited from an otolaryngology department in a UK Teaching Hospital. All patients had failed medical therapies for chronic rhinosinusitis (CRS), recurrent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
15
2
Order By: Relevance
“…CRS is a debilitating disease and its diagnosis is based on subjective and objective criteria. To date, studies are mixed regarding the correlation between inflammation, as seen on CT, and CRS symptoms . In this study we found evidence for an association between LMCTS and pre‐ and postoperative sinonasal quality of life, as measured by the SNOT‐22.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…CRS is a debilitating disease and its diagnosis is based on subjective and objective criteria. To date, studies are mixed regarding the correlation between inflammation, as seen on CT, and CRS symptoms . In this study we found evidence for an association between LMCTS and pre‐ and postoperative sinonasal quality of life, as measured by the SNOT‐22.…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have concluded that there is little concordance between CT and total symptom–based scores, which implies that increased mucosal inflammation does not correlate with increased symptom severity. However, some of these same studies, as well as others, have shown significant correlation between CT scores and specific symptoms .…”
mentioning
confidence: 99%
“…The two constructs (rhinologic, ear & facial domains) address symptoms and two others (sleep and psychological domains) address aspects of health related quality of life. The above 2 studies show effectiveness of FESS in CRS patients and the efficacy of FESS has been established by many other studies with large no of patients [10]. Other studies by Net kovski et al (2006) [13], Chopra H. et al (2006) [14], Venkatraman V et al (2013) [15] revealed significant symptomatic improvement after FESS and its efficacy in CRS patients.…”
Section: Discussionmentioning
confidence: 85%
“…A study by Murthy P.et al (2013) [10] showed the symptoms of facial pain, headache, nasal obstruction, nasal discharge, smell disturbance and overall discomfort improved with statistical significance (p<0.001) but most improved were nasal obstruction and facial pain. National audit of sinus surgery's report was published by the Royal College of Surgeons of England, which reported rates of improvement in nasal obstruction of 84% and pain in 75%.…”
Section: Discussionmentioning
confidence: 97%